2018
DOI: 10.1039/c8ra02804d
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of secondarily structured oligonucleotides to single-stranded rings by using Taq DNA ligase at high temperatures

Abstract: We have achieved the efficient preparation of single-stranded DNA rings from secondarily structured oligonucleotides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The efficiency of the cyclisation reaction is sensitive to the length of the linear DNA precursor, and is inefficient if the nucleobase sequence leads to secondary structures. 25 , 26 In addition, the scale on which the cyclisation reaction can be carried out is limited by the cost of the enzyme. In principle these limitations could be circumvented by the use of chemical ligation ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the cyclisation reaction is sensitive to the length of the linear DNA precursor, and is inefficient if the nucleobase sequence leads to secondary structures. 25 , 26 In addition, the scale on which the cyclisation reaction can be carried out is limited by the cost of the enzyme. In principle these limitations could be circumvented by the use of chemical ligation ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such long complementary ends were believed to be necessary to make the T m of the corresponding duplexes (about 66–70 °C) comparable with (or slightly higher than) the ligation temperature. Accordingly, DNA fragments longer than 20 nt were ligated at 65 °C in Tth DNA ligase-based LCR, LDR, and other studies. Only the cyclization of ssDNA was accomplished at 65 °C using an 18-nt-long splint (and thus 18 bp complementary portion) . However, unexpected findings in this paper showed that Tth DNA ligase has high ligation efficiency at 65–80 °C, even when the complementary portions of substrate DNAs are much shorter (7–10 nt).…”
Section: Discussionmentioning
confidence: 94%
“…31−36 Only the cyclization of ssDNA was accomplished at 65 °C using an 18nt-long splint (and thus 18 bp complementary portion). 37 However, unexpected findings in this paper showed that Tth DNA ligase has high ligation efficiency at 65−80 °C, even when the complementary portions of substrate DNAs are much shorter (7−10 nt). The "free ssDNA" ligation of Fss-γ 7 was successful even at 70 °C, which is much higher than the T m of the corresponding duplexes (around 39 °C, Table S4).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Recently, we reported that secondarily structured oligonucleotides can be successfully cyclized by using thermostable Taq DNA ligase at high temperatures (34). The ‘terminal hairpin strategy’ in this study is a significant extension in that secondary structures of DNA are successfully used as gate keeper to hold on intermolecular polymerization which is a significant problem for effective preparation of DNA rings.…”
Section: Discussionmentioning
confidence: 99%
“…The data were analyzed by Image Lab software to quantify the fluorescence emission from each band. The calculating methods of selectivity and yield were the same as our last papers (30,34). The conversion for the formation of DNA rings were calculated by the following equation: \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{equation*}{\rm{Conversion}}\,\left( \% \right){\rm{ }} = {\rm{ }}(1 - \frac{R}{{P + C + R}}) \times 100,\end{equation*}\end{document}where C, P and R are the band intensities of circular single-stranded DNA ring, polymeric byproducts and remained single-stranded linear DNA (l-DNA), respectively.…”
Section: Methodsmentioning
confidence: 99%